PENGARUH PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DI PT. PENDIDIKAN MARITIM DAN LOGISTIK INDONESIA TERHADAP PRODUKTIVITAS KERJA PESERTA - Hanif Ahsanu Amal; Henita Rahmayanti (LOGISTIK, 2021)
The purpose of this study was to determine the effect, respondents' responses and sub-variables that influence training and human resource development on work productivity held in PT. Pendidikan Maritim dan Logistik Indonesia through questionnaire data. The method used is descriptive quantitative method with primary and secondary data through statistical analysis. Collecting data by distributing questionnaires to respondents to get perceptions of the training that was followed. From the results of the research conducted, it can be concluded that the implementation of training and human resource development held at PT. Indonesian Maritime and Logistics Education has an effect on the work productivity of participants by 3.75 and is categorized as quite high in its implementation. Therefore, the training provided to the participants should produce a reliable workforce or human resources compared to the disciplines of each employee in order to achieve the company's goals.